Alternative Policy on Progressive Tax Rate on Idle Land in the Special Capital Territory of Jakarta - Rizki Nanda Apriani; Inayati Inayati (Jurnal Administrasi Publik (Public Administration Journal), 2020)
The objective of this study is to analyze the alternative progressive tax rates on idle land in DKI Jakarta. Researchers used qualitative method. Based on the results of the analysis through data collection carried out using literature studies and in-depth interviews with informants, it can be concluded that with this progressive tax rate policy alternative it is believed that it can suppress effectively and precisely the concentration pattern of land ownership and control as well as speculative behavior towards land and legal entities that hoard the land. These laws and government regulations were inadequate to be applicable to non-agricultural lands or lands with ownership, or use rights. It is due to  both of them have not regulated the extent of non-agricultural land, as well as the area of land ownership rights, building use rights, and use rights either for individual or legal entities. The imposition of a progressive tax rate by looking at the length of ownership adopted by South Korean country was also considered capable of being a pretty good way dealing with this idle land problem. The results of study related to the imposition of a progressive tax rate on idle land using the excess scheme or additional collection on the building land tax has been previously imposed.